Refusal of medical treatment: assessing the required capacity - Jahn Kassim, Puteri Nemie (LexisNexis Sdn Bhd, 2007)
The right to undertake or refuse medical treatment presupposes a capacity to do so. Every adult is presumed to have that capacity, but it is a presumption that can be rebutted. Some patients may not possess the necessary capacity due to their mental illness or retarded development or simply because they are under the age of majority. Problem usually arises with patients who have the necessary capacity but may be deprived of it or have it reduced by reason of temporary factors, such as unconsciousness, confusion or other effects of shock, severe fatigue, pain or drugs being used in their treatment. Medical professionals faced with a refusal of consent have to give very careful and detailed consideration to the patient’s capacity to decide at the time when the decision was made. It may not be the simple case of the patient having no capacity but the more difficult case of a temporarily reduced capacity at the time when the decision was made, particularly, in relation to pregnant women and persons bound by certain religious beliefs.